Distributed earth fault detection method for low voltage distribution networks using phase voltage synchronization - Zhongyu Sun; Bingyin Xu; Wei Wang; Tony Yip; Fan Li (International Journal of Electrical Power & Energy Systems)
The existing earth fault detection methods for low-voltage distribution networks demonstrate poor adaptability to faults with fault resistance. To address this problem, the composition of residual current during non-fault states and its impact on earth fault detection are analysed. A distributed earth fault detection method is then proposed. This method divides a low-voltage distribution network into multiple protection zones and uses the differential residual current of each protection zone to identify earth faults, effectively reducing the impact of residual current during non-fault states. Furthermore, a time synchronization technique using phase voltage as a reference is proposed, which achieves low-cost time synchronization without relying on external clocks. The effectiveness of the proposed method is verified by simulations and field tests in an actual low-voltage platform. Compared with conventional approaches, the proposed method exhibits significant enhancements in both sensitivity and reliability.